ON LOCALIZATION OF BILISTAN FORTRESS - Gadziev, Murtazali Serazutdinovic; Abdulgamidov, Nizami Abdulgamidovic (History, Archeology and Ethnography of the Caucasus, 2019)
Abstract. The article is dedicated to the localization of the fortress Bilistan that was besieged by Arabian forces lead by Marwan ibn Muhammad, deputy of Arminiya and Azerbaijan, in spring 783 A.D. during his military campaigns in the Eastern Caucasus and in which King of Lakz Arbis ibn Basbas took refuge. According to Abu Muhammad Ahmad ibn A’sam al-Kufi’s Kitab al-Futuh (The Book of Conquests), this fortified settlement was located in the «Land of Lakz» at the middle of the river Samur. The authors suggest localizing the Bilistan fortress (from the Persian/Tati – «place, settlement in lowland») in the area of the Lezgin village Quysun that has a second name Quyustan. The village has strategic value in the Samur valley bordering with plains and foothills. The name Quyustan is of Turkic origin and is a Turkic calque of a Persian word for «place, a settlement near the river valley» (Old Turkic quj / qoj – «bottom of the valley», i.e. «lowland»). The other name of this village (Quysun) is of Turkic-Mongolian origin and means «place on the verge of the river valley». The names of these three semantically and geographically interrelated toponyms belong to three different chronological levels and reflect certain political dominants and cultural and linguistic influences during these periods: Persian Bilistan, which is, clearly, relates to the times of Khosrow Anushirwan’s reign (mid. of VI cent.); Turkic-Persian Quyustan, which, supposedly, dates back to the Seljuq Empire (XI-XII cent.); Turkic-Mongolian Quysun, which seemingly appeared in the Mongolian/Golden Horde period (XIII-XIV cent.).
Keywords: al-Kufi; Kitab al-Futuh; Early Muslim conquests; Marwan ibn Muhammad; Daghestan; Lakz; Bilistan.